Anterior and antero-lateral mini-invasive approaches for primary total hip replacement - Ponziani, Lorenzo; Di Caprio, Francesco; Tentoni, Francesco; Grana, Simone; Di Meo, Antimo; Gigli, Marina (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: the literature provides conflicting data regarding the various approaches for hip prosthetic surgery. This study analysed our case series on the anterior and anterolateral minimally invasive approaches, trying to define the indications, complications, the technical tips, the advantages and disadvantages.Methods: from 2011 to 2019 we performed 1227 interventions of which 1020 had a regular follow-up, up to an average period of 5.1 years. 625 anterolateral and 395 anterior approaches were performed, of which 149 with longitudinal incision and 246 with an oblique “bikini” incision.Results: the Harris Hip Score showed similar results in the two groups, except from the early post-operative period, which showed slight superior results for the anterior approach. Surgical times were in favour of the anterolateral approach, while hospitalization times were less for the anterior approach. With the anterior approach, we recorded a greater number of complications, in particular malpositioning, periprosthetic fractures and neurological injuries, especially in the first two years of experience.Conclusions: there was no clear superiority of one approach over another. We conclude that the surgeon should know both techniques, to be adapted to the type of patient in consideration of the size and deformity. The traction bed provides more disadvantages than advantages, and in our experience it is not recommended.